Acoustic and magnetic properities dependence of restructuring differents magnetic fluids subjected to external magnetic fluid - Regulska, P.; Skumiel, A.; Józefczak, A. (Archives of Acoustics, 2006)
The influence of magnetic field intensity and temperature on acustic and magnetic proprieties was considered. Measurements were conducted at an ultrasonic wave frequency of 3.6 MHz, by a pulse method using the MATEC apparatus. The direction of ultrasonic wave propagation was parallel to the direction of the external magnetic field. The magnetic field range was 10–150 kA/m. The studies were performed for a selected temperatures. The results of this experiments suggested that in magnetic fluids there are different effects connect with restructuring this fluids.